Study of Porosity and Mechanical-Elastic Properties of the Potential Underground CO2 Storage in Un-Mined Coal Seams from Well-log Data, South Sumatra Basin, Indonesia - Handoyo, Handoyo; Sigalingging, Asido Saputra; Nathania, Edlyn Yoadan; Astomo, Dimas; Carbonell, Ramon; Samosir, Sondang (Science and Technology Indonesia, 2025)
In CO2 storage technology, particularly in coal seams, necessitates specialized research into numerous critical factors that are equivalent to coal seam characteristics, including porosity, permeability, rock strength (UCS: uniaxial compressive strength), Poisson ratio, and brittleness. Rock properties of the coal seam are responsible for the CO2 storage capacity. In this study, we have core samples from the borehole and employed four well-logs (within and area ∼ 1000 m × 875 m) that drilled in the coal mining project located in South Sumatra Basin, Indonesia. The goal of this study is to describe the coal seam C strata in the sub-surface that have the potential to be utilized for underground CO2 storage. In this study, we identified coal seams C from low density and gamma rays from log response data. Then, we predict porosity values from data density, velocity (Vp andVs), UCS values, and BI using petrophysical and rock physics approaches. The result of this study shows that the distribution of top depth coal seam C varies in depth 19 to 225 m with the porosity 0.086-0.138. The value of UCS 1150 1299 Pa and brittleness index 0.531-0.569 that are associated with a characteristic coal with low to medium strength and medium brittleness. The results of this preliminary analysis revealed that the coal seam layer in this region has a high potential for CO2 storage in Sumatra, Indonesia.